Persistent COVID-19 symptoms are highly prevalent 6 months after hospitalization: results from a large prospective cohort. (July 2021) - Ghosn, Jade; Piroth, Lionel; Epaulard, Olivier; Le Turnier, Paul; Mentré, France; Bachelet, Delphine; Laouénan, Cédric; ,
Abstract: Objectives: Persistent COVID-19 symptoms have been reported up to 3 months after hospital discharge. Little is known on the frequency and the nature of persistent symptoms beyond 3 months. Here we have assessed, in the longitudinal prospective French COVID-19 cohort, symptoms that persisted 6 months after admission for COVID-19. Methods: Hospitalized patients with virologically confirmed COVID-19 were enrolled. Follow-up was planned with a physician's visit at month (M)3 and M6 after admission. Associations between persistence of symptoms at M6 and clinical characteristics at admission were assessed through bivariate and multivariate logistic regression. Results: M6 data were available for 1137 participants. Median age was 61 years (IQR 51–71) and 288 (29%, 95% CI 26–32%) were admitted to intensive care unit (ICU) during the acute phase. Six hundred and fifty-five (68%, 95% CI 65–71%) and 639 (60%, 95% CI 57–63%) participants had at least one symptom at M3 and M6 visit, respectively, mostly fatigue, dyspnoea, joint pain and myalgia. At M6, 255 (24%, 95% CI 21–27%) of participants had three or more persistent symptoms. The presence of three or more symptoms at M6 was independently associated with female gender (adjusted odds ratio (aOR) 2.40, 95% CI 1.75–3.30), having three or more symptoms at admission (aOR 2.04, 95% CI 1.45–2.89) and ICU admission/transfer during acute phase (aOR 1.55, 95% CI 1.09–2.18), but not significantly with age or having two or more comorbidities. One hundred and twenty-five (29%, 95% CI 25–34%) of those who initially had a professional occupation were not back to work at M6. Discussion: A fourth of individuals admitted to hospital for COVID-19 still had three or more persistent symptoms at M6. Longitudinal follow-up of individuals with severe COVID-19 is warranted to better understand the pathophysiology underlying this long-term persistence.